AKTUALISASI SISTEM PERTAHANAN RAKYAT SEMESTA (SISHANTA) DAN DINAMIKA POTENSI ANCAMAN - Yudi Rusfiana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Sishanta can be actualized in the face of all the dynamics of potential threats to national defense that are rapidly developing in line with the development of the strategic environment that can create threats that are not only military threats, but also non-military ones. Threats are not only traditional but also non-traditional. The formation of a reserve component (komcad) as an element of non-military defense forces, is functioned to assist the main component (computing) of national defense (TNI). The reserve component is a solution to deal with potential military threats in the context of the fifth and even sixth generation wars that are non-military. Furthermore, state defense in this case is useful as the main teaching material given to members of the state defense reserve component so that through this effort Sishanta as a state defense system can be actualized. Because the involvement of citizens in the effort to defend the country is part of the responsibility of citizens. This responsibility is impliedly mandated by the constitution, as well as Law no. 3 of 2002 on National Defense. With the aim of maintaining the survival of the nation and state.